2021
DOI: 10.1891/0730-0832/11-t-678
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Spectroscopy: Clinical Use in High-Risk Neonates

Abstract: In this review, we describe the near-infrared spectroscopy (NIRS) technology and its clinical use in high-risk neonates in critical care settings. We searched databases (e.g., PubMed, Google Scholar, EBSCOhost) to find studies describing the use of NIRS on critically ill and high-risk neonates. Near-infrared spectroscopy provides continuous noninvasive monitoring of venous oxygen saturation. It uses technology similar to pulse oximetry to measure the oxygen saturation of hemoglobin in a tissue bed to describe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Although NIRS has a wide range of applications in the medical field, such as brain function monitoring ( Grossmann, 2008 ; Holper et al, 2019 ), muscle oxygenation monitoring ( Klusiewicz et al, 2021 ), cardiac function monitoring ( Ortega-Loubon et al, 2019 ), neonatal care ( Tran et al, 2021 ), there are rare reports on liquid biopsy- based NIRS for cancer diagnosis. Our previous studies ( Zhu et al, 2023 ; Chen et al, 2021 ) showed a promising diagnostic value in cancer using plasma or pleural effusion.…”
Section: Discussionmentioning
confidence: 99%
“…Although NIRS has a wide range of applications in the medical field, such as brain function monitoring ( Grossmann, 2008 ; Holper et al, 2019 ), muscle oxygenation monitoring ( Klusiewicz et al, 2021 ), cardiac function monitoring ( Ortega-Loubon et al, 2019 ), neonatal care ( Tran et al, 2021 ), there are rare reports on liquid biopsy- based NIRS for cancer diagnosis. Our previous studies ( Zhu et al, 2023 ; Chen et al, 2021 ) showed a promising diagnostic value in cancer using plasma or pleural effusion.…”
Section: Discussionmentioning
confidence: 99%
“…NIRS is an indirect measure of oxygenation and therefore has several limitations of its application when there is movement, low arterial oxygen levels, darker skin pigmentation, or changes in weight and/or edema ( 146 ). Perhaps the biggest limitation is that there are no established standards and specific guidelines for use and interpretation of NIRS in neonates are lacking.…”
Section: Methods Of Oxygen Measurement and Titrationmentioning
confidence: 99%